Some Thoughts on Training Programmes for Modernising Library and Information Systems and Services in India - Rajan, T. N. (Journal of Information and Knowledge, 1987)
Focusses attention on formulating plans and policy for building up a manpower force for modernising library and information systems and services in India within the next five years. Enumerating the areas of modernisation in the Indian context and the types of personnel required, examines the requirement in terms of operational and intellectual inputs. Briefly describes the types of courses to be designed. Summarises the parameters in a three dimensional schematic cube.